Educational Robotics in Times of Pandemic: Challenges and Possibilities - Gomes, Andressa Shirley; da Silva, Joice; Teixeira, Leonardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Due to the personal and material restrictions caused by the COVID-19 pandemic, the teaching of robotics has been greatly affected in recent months due to its practical nature. This work aims to explore possibilities for the continuation of this teaching remotely. A simple teaching methodology will be proposed, listed and compared simulators softwares on the most diverse platforms, and the possibility of using remote laboratories will be analyzed. The idea is to present a set of solutions, so that teachers can analyze and select the possibilities that best identify themselves and that best suit the specifics of their class.